Linguistic and cultural continuum of the word «avitaminosis» in the russian language worldimage - Katermina Veronika V.; Makeeva Mariya A. (Current Issues in Philology and Pedagogical Linguistics, 2018)
The article is devoted to the issue of information structuring within the concept «Ecology». Each concept contains various information which constitutes the core and the periphery of the concept and is actualized in the person’s picture of the world. The same information can be regarded differently; the reason is a partial discrepancy in pictures of the world and the difference of gained experience. The information within the concept consists not only of proved knowledge but of associations and representation of each individual as well. Thus, the quantity of information within the concept is considerably large. To systematize the knowledge within the concept models of knowledge representation were introduced; a frame is an example of such a model. In the following article a frame is regarded as a schematic representation of knowledge within the concept consisting of the frame’s name and its slots – well-ordered units which organize the structure of the frame. Having studied frames as the unit of knowledge representation attention is drawn to the peculiarities of frame perception which are determined by their recipients’ characteristics. The names of the slots are usually common for frames of one thematic group unlike their content which is unique for slots of different frames. On the basis of the comparative analysis of «Global warming» frame in Australian and Arctic representatives’ pictures of the world the conclusion has been made that this frame unfolds to its recipients differently due to their location, experience and urgency of the problem in each country.